The Effect of Electronic Word of Mouth and Social Media on the Decision to Visiting With Destination Image as a Mediating Variable - Inna Mutmainna Cahyani Thahir; Rahman Kadir; Nuraeni Kadir (Magister Management, Hasanuddin University, 2021)
This study aims to determine the effect of electronic word of mouth and social media on the decision to visit Kemeparekraf's Youtube channel subscribers with destination image as a mediating variable. The study applied purposive sampling. Questionnaire distributed to 85 respondents using a five-Likert scale. Path analysis test is evaluated using SPSS version 21 program. The result shows that electronic word of mouth had a positive and significant effect on destination image and has the same effect on visiting decisions. Social media has a positive and significant effect on the image of the destination and on the decision to visit. The image of the organization's destination has a positive effect on the decision to visit. Both electronic word of mouth and social media show an effect on nurse performance through destination image.